2014
DOI: 10.1002/2014jc010014
|View full text |Cite
|
Sign up to set email alerts
|

Internal tide radiation from the Luzon Strait

Abstract: The M 2 , K 1 , and O 1 internal tides originating in the Luzon Strait are investigated using the sea surface height measurements by multiple satellites ERS-2, Envisat, TOPEX/Poseidon, Jason-1/2, and Geosat Follow-On. A plane wave fit method is used to resolve multiple internal tides in arbitrary horizontal directions. The Luzon Strait is an energetic internal tide generation site, and radiates internal tides both westward into the South China Sea (SCS) and eastward into the western Pacific (WP). In the SCS, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
136
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(166 citation statements)
references
References 72 publications
(79 reference statements)
28
136
2
Order By: Relevance
“…For understanding the characteristics of the internal wave spectrum, the vertical displacement of the isothermal was extracted from the time series of temperature, and then the frequency spectra of internal wave displacement at different depths were calculated and compared with Garrett and Munk (GM) spectrum in oceans (Garrett & Munk 1972, 1975 (Figure 6). Remarkable peak values of the displacement spectrum exist in diurnal and semidiurnal frequencies that are consistent with some previously reported research (Zhao, 2014). The energy level of the spectrum was larger than 10 5 m 2 /(rand/s) over the frequency band less than the semidiurnal frequency; beyond this frequency, the spectrum level was smaller than 10 5 m 2 /(rand/s), and this phenomenon occurred at all depths.…”
Section: Sea Trialsupporting
confidence: 92%
“…For understanding the characteristics of the internal wave spectrum, the vertical displacement of the isothermal was extracted from the time series of temperature, and then the frequency spectra of internal wave displacement at different depths were calculated and compared with Garrett and Munk (GM) spectrum in oceans (Garrett & Munk 1972, 1975 (Figure 6). Remarkable peak values of the displacement spectrum exist in diurnal and semidiurnal frequencies that are consistent with some previously reported research (Zhao, 2014). The energy level of the spectrum was larger than 10 5 m 2 /(rand/s) over the frequency band less than the semidiurnal frequency; beyond this frequency, the spectrum level was smaller than 10 5 m 2 /(rand/s), and this phenomenon occurred at all depths.…”
Section: Sea Trialsupporting
confidence: 92%
“…Our mooring observations, as well as satellite observations (Zhao, 2014) and CELT model simulations, suggest that diurnal internal tides generated in Luzon Strait propagate westward to the southwest-northeast slope on the east side of Dongsha Island, break near the bottom due to critical-supercritical reflection, and generate southwestward along-slope currents (Figure 5a). The westward traveling semidiurnal internal tides also obliquely impact the southwest-northeast slope.…”
Section: Discussionmentioning
confidence: 71%
“…In this paper, we focus on internal tides impinging on the continental slope in the northeastern South China Sea (SCS). Satellite altimeter observations have revealed that low-mode internal tides generated in Luzon Strait obliquely travel onto the continental slope on the east side of DongSha Island (Figure 1; Zhao, 2014). Satellite altimeter observations have revealed that low-mode internal tides generated in Luzon Strait obliquely travel onto the continental slope on the east side of DongSha Island (Figure 1; Zhao, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Internal waves are unevenly distributed throughout the SCS. Most of the internal waves and internal tides originate in the Luzon Strait and propagate northwestwards through the deep water zone near the Luzon Strait to the continental shelf (Guo and Chen, 2014;Klymak et al, 2006b;Lien et al, 2005;Ramp et al, 2004;Zhao, 2014;Zhao et al, 2004). Internal wave packets derived from satellite images by Zhao et al (2004) are shown in Fig.…”
Section: Microstructure Measurementsmentioning
confidence: 99%